Topical drug therapeutics for neuropathic pain. (24th July 2018) - Coderre, Terence J.
ABSTRACT: Introduction : Neuropathic pain (NP) is a particularly severe and intractable chronic condition that is not well treated by commonly recommended systemic pharmacological therapies, partly due to dose-limiting side effects or adverse events. The use of topical therapeutics for NP is growing and benefits from the reduced potential for adverse effects, as well as the ability to directly target peripheral pathological processes. Areas covered : The current review defines and describes the limitations of various commonly prescribed systemic pharmacological therapies for NP. It also provides a justification for increased research aimed at developing topical therapeutics for NP, particularly localized and peripheral NP. The review discusses the various classes of topical treatments used for NP, including agents that: block sensory inputs; activate inhibitory systems; provide mechanism-based therapeutics; are used in mucosal tissues; and include combinations that produce multimodal therapeutic effects. Expert opinion : There are arguments that the current topical therapeutics for NP rely too heavily on the use of local anesthetics and capsaicinoids, and more research is certainly needed on topical therapies that are multimodal and/or are targeted at the peripheral sources of pathology. The potential for novel topical therapeutics may be enhanced by further research on topical co-drugs, drug-drug salts, co-crystals and hydrates, and ionic liquids.